Lessons learned from implementation of an electronic decision support tool for hospital-administered pneumococcal vaccinations - Sanchi Malhotra; Rachel Martin-Blais; Ross Pineda; Meganne Kanatani; Ishminder Kaur; Annabelle de St. Maurice (Cambridge University Press, 2024)
Experts recommend standing orders for hospital-administered vaccines to improve adult immunization rates. We implemented an admission assessment tool to offer pneumococcal vaccine to eligible hospitalized patients. We retrospectively reviewed vaccines for guideline concordance and found that immunization rates increased but less than half of study patients received the correct vaccine.